Efficacy of Repeated Courses of Antiviral and Immunotropic Therapy in Children with Hematuric Form of Chronic Glomerulonephritis and Chronic Epstein - Barr Virus Infection - T.P. Borisova; Ye.N. Tolchennikova (Zaslavsky O.Yu., 2013)
The purpose of research - to estimate the efficacy of repeated courses of antiviral and immunotropic therapy in children with hematuric form of chronic glomerulonephritis (HFCGN) and concomitant chronic Epstein - Barr viral infection (EBVI). 54 children with HFCGN and chronic EBVI aged 3-17 years were examined. Patients received preparation of recombinant interferon (IFN) α-2β and a medication containing flavonoids Deschampsia caespitosa L. and Calamagrostis epigeios L., at presence of signs of activity of chronic EBVI activity signs patients were also administered with acyclovir. Duration of therapy - 3 months. Number of courses - 3. A break between courses of treatment was three months. Treatment efficacy was assessed by means of nephrological, virological and immunological examination before treatment, in 6, 12 and 18 months of follow-up, i.e. in 3 months after completion of the first, second and third courses of treatment. Use of repeated courses of antiviral and immunotropic therapy in children with HFCGN and chronic EBVI led to a decrease in the severity of erythrocyturia, frequency of macrohematuria, tubular disorders, normalizing levels of IFN-α, IFN-γ, IL-1β in blood serum and a significant decrease in the concentration of IL-6. Significant positive changes in the state of children's health is marked after the third course of therapy, which manifested in reduction of incidence rate of respiratory diseases, the frequency of asthenic syndrome, lymphadenopathy, tonsillitis, adenoiditis, hepatomegaly, cardiopathy, liquidation of low-grade fever, splenomegaly.